(untitled) (Journal of Economic Research & Business Administration, 2019)
One of the main trends of modern reality is the rapid growth rate of the service sector. The modern level of development of the leading countries of the world shows the dynamic development of the service sector and their market, and the level of development of the service sector is a criterion of social progress. The development of the service sector and its improvement in meeting the needs of society are directly related to innovation. Also one of the indicators of the development of the service sector is the competitiveness of services, which is associated with the level of innovation in each service enterprise. The purpose of the study is to determine the prospects for the development of new forms and methods of customer service of JSC «Kazakhstan Temir Zholy» on the basis of innovative activity. The processes of globalization and changing technological structures form modern challenges for railway transport. The development of information and telecommunication systems, high-speed rail transportation technologies, globalization and optimization of logistics chains with the integration of various types of transport create the prerequisites and opportunities for a fundamental transformation of railway transport. When writing the article, the works of domestic and foreign scientists, materials of scientific and practical conferences, information resources of the Internet were used. The article discusses the innovative activity of the enterprise, innovative forms of service of JSC «Kazakhstan Temir Zholy». Proposed measures to improve the innovative forms of service JSC «Kazakhstan Temir Zholy».